Employing algal extract for the fabrication of bimetallic nanoparticles: A powerful solution against tomato pathogenic fungi - Reham M. Aldahasi; Kawther Aabed; Sahar S. Alghamdi; Afrah E. Mohammed (AIP Advances)
This study explores the innovative use of an aqueous spirulina and chlorella mixture to synthesize bimetallic zinc/manganese nanoparticles (ZnO–Mn NPs), showcasing a sustainable approach to nanomaterial development. The nanoparticles were thoroughly characterized using advanced techniques, including UV–visible spectrophotometry, Fourier transform infrared spectroscopy (FTIR), dynamic light scattering, scanning electron microscopy, transmission electron microscopy, and energy-dispersive x-ray spectroscopy. These analyses revealed that the ZnO–Mn NPs have an average size of 314.4 nm, a polydispersity index of 0.28, and a zeta potential of −23.86 mV, indicating excellent stability and a uniform distribution. The antifungal properties of the synthesized nanoparticles were tested in vitro against key tomato pathogens, Sclerotinia sclerotiorum and Fusarium equiseti. FTIR analysis highlighted the role of phytochemicals from the algal extracts in the reduction and capping of nanoparticles. While the antifungal activity observed was modest at the evaluated concentrations, the strong stability and biocompatibility of the nanoparticles underscore their potential as eco-friendly solutions in agricultural applications. This research highlights the promise of utilizing natural extracts to develop effective nanoparticles, offering a greener alternative for managing plant diseases and enhancing sustainable farming practices.